疫情背景下對待無症狀感染者的道德困境與出路探究: Moral Dilemma and Outlet for Treating Asymptomatic Infected Persons against the Background of the Epidemic - ZHANG, Yanliang (International Journal of Chinese & Comparative Philosophy of Medicine, 2020)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 筆者在這篇文章中主要處理的是在疫情背景下對待無症狀感染的道德困境和道德出路問題。筆者首先介紹了研究這一問題的背景；其次，對於無症狀感染者以及對於無症狀感染者所採取的措施進行了事實性的描述；第三，對於對待無症狀感染者所採取的措施可能帶來的道德困境進行了分析；最後，對於如何走出對待無症狀感染者的道德困境進行了探索。 In this article, the author outlines the moral dilemma and moral outlet of treating asymptomatic infected persons against the background of the epidemic. The author first introduces the background of the research on this problem and then provides a factual description of asymptomatic infected persons and the measures taken for the asymptomatic infected persons. Then, the author analyzes the moral dilemmas that may arise from the measures taken to treat asymptomatic infected persons. Finally, the author explores how to resolve the moral dilemma of treating asymptomatic infected persons. DOWNLOAD HISTORY | This article has been downloaded 18 times in Digital Commons before migrating into this platform.